Do human activities affect phytoplankton biomass and composition in embayments on Lake Diefenbaker?. Issue 4 (1st October 2016) - Abirhire, Oghenemise; North, Rebecca L.; Hunter, Kristine; Vandergucht, David; Hudson, Jeff
ABSTRACT: Lake Diefenbaker (LD) is an important source of water for southern Saskatchewan. LD is characterized by numerous embayments containing anthropogenic activities (e.g., housing, marinas, cattle watering). Many of these activities are increasing on this important reservoir in association with the rapidly developing economy of Saskatchewan. These activities may reduce water quality directly or indirectly by encouraging the growth of nuisance algae (i.e. cyanobacteria). Here, we examined phytoplankton biomass and composition in eight embayments exposed to anthropogenic activities, four unexposed embayments with no perceived human activities and six main channel sites adjacent to the embayments from June to October (2011 and 2012). Phytoplankton biomass and composition was not significantly different in exposed, unexposed embayments and main channel sites ( p > 0.05), with the diatoms and cryptomonads constituting 87%–91% of the total phytoplankton biomass in both years. High flows from the South Saskatchewan River (SSR) in both years may have resulted in the rapid flushing of the embayments and dampened any localized impacts that could have resulted from anthropogenic activities as found in other studies. Hence, future study on LD should be conducted during years with low flow from the SSR when the rate of flushing of embayments will be reduced.